Resolving the graft ischemia-reperfusion injury during liver transplantation at the single cell resolution - Wang, Linhe; Li, Jie; He, Shuai; Liu, Yang; Chen, Haitian; He, Shujiao; Yin, Meixian; Zou, Dawei; Chen, Shirui; Luo, Tao; Yu, Xinyu; Wan, Xuesi; et al. (Cell death & disease, 2021)
Ischemia–reperfusion injury (IRI) remains the major reason for impaired donor graft function and increased mortality post-liver transplantation. The mechanism of IRI involves multiple pathophysiological processes and numerous types of cells. However, a systematic and comprehensive single-cell transcriptional profile of intrahepatic cells during liver transplantation is still unclear. We performed a single-cell transcriptome analysis of 14,313 cells from liver tissues collected from pre-procurement, at the end of preservation and 2 h post-reperfusion. We made detailed annotations of mononuclear phagocyte, endothelial cell, NK/T, B and plasma cell clusters, and we described the dynamic changes of the transcriptome of these clusters during IRI and the interaction between mononuclear phagocyte clusters and other cell clusters. In addition, we found that TNFAIP3 interacting protein 3 ( TNIP3) , specifically and highly expressed in Kupffer cell clusters post-reperfusion, may have a protective effect on IRI. In summary, our study provides the first dynamic transcriptome map of intrahepatic cell clusters during liver transplantation at single-cell resolution.